Organo-photoredox catalyzed oxidative dehydrogenation of N-heterocycles - Sahoo, Manoj K.; Jaiswal, Garima; Rana, Jagannath; Balaraman, Ekambaram (Chemistry-A European Journal, 2017)
We report here for the first time the catalytic oxidative dehydrogenation of N-heterocycles by a visible-light organo-photoredox catalyst with low catalyst loading (0.1-1mol%). The reaction proceeds efficiently under base- and additive-free conditions with ambient air at room temperature. The utility of this benign approach is demonstrated by the synthesis of various pharmaceutically relevant N-heteroarenes such as quinoline, quinoxaline, quinazoline, acridine, and indole.